(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Medical education demands rapid adaptation to complex curricula, making the understanding of individual learning styles crucial for optimizing student performance. The VARK model (Visual, Aural, Read/Write, Kinesthetic) provides a framework to assess these preferences, yet studies on medical undergraduates remain limited. This study aimed to identify the preferred sensory modalities for learning and explore potential differences across gender and academic years. Methods: A cross-sectional study was conducted among third- and final-year medical students using the pre-validated VARK questionnaire (Version 8.0). The questionnaire assessed preferences for unimodal (single style) or multimodal (combined styles) learning. Data were analyzed to determine associations between learning styles, gender, and year of study using chi-square tests. (SPSS version 20.0, p<0.05 considered significant). Results: Among 200 participants, 86% preferred multimodal learning, with bimodal combinations (e.g., RA [18%], VA [16%], AK [13.5%]) being most common. Unimodal learners (14%) predominantly favoured the kinaesthetic style (6%). No significant associations were found between learning preferences and gender (p=0.08) or year of study (p=0.3). However, final-year students showed a preference for RA and VA bimodal styles, while third-year students favoured AK (p=0.0007). Conclusion: Most medical students exhibited multimodal learning preferences, underscoring the need for diverse teaching strategies that integrate visual, auditory, read/write, and kinaesthetic elements. These findings advocate for curriculum reforms aligned with the National Medical Commission’s competency-based approach, emphasizing adaptable methodologies to enhance engagement and academic outcomes. Future research should investigate longitudinal trends and the impact of tailored interventions on clinical skill acquisition.